2014
DOI: 10.5935/1676-4285.20144979
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and people using antineoplastic agents: a descriptive study

Abstract: RESUMOObjetivos: avaliar a qualidade de vida das pessoas que apresentaram náuseas e vômitos induzidos por antineoplásicos e correlacionar a qualidade de vida com o potencial emetogênico do protocolo quimioterápico e com o dimensionamento do esquema antiemético. Método: estudo descritivo, quantitativo, realizado em um ambulatório de onco-hematologia de um hospital do município de São Paulo. Foi utilizado o questionário SF-36 para avaliar a qualidade de vida dos indivíduos e um questionário de caracterização da … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
9
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…It is known that the cancer or the mere possibility of having a malignant tumor leads one to despair, fear, distress, hopelessness, sadness, nervousness. 4,6 A survey conducted in order to evaluate the level of stress in women with mastectomies, in assessing stress in 84 patients, found that 69,0% of them were with stress. 18 Similar to our study.…”
Section: Stress In Patients …mentioning
confidence: 99%
See 4 more Smart Citations
“…It is known that the cancer or the mere possibility of having a malignant tumor leads one to despair, fear, distress, hopelessness, sadness, nervousness. 4,6 A survey conducted in order to evaluate the level of stress in women with mastectomies, in assessing stress in 84 patients, found that 69,0% of them were with stress. 18 Similar to our study.…”
Section: Stress In Patients …mentioning
confidence: 99%
“…11 Nausea was one of the side effects most frequently reported by patients (16,0%), it is a very common effect in chemotherapy, often responsible for the anxiety and stress of it, because, in most cases, is accompanied by symptoms such as pallor, weakness, dizziness and sweating thus causing a general malaise, making it more difficult to face the patient's treatment. 4 Research conducted in the United States pointed out that the nausea and vomiting induced by antineoplastic is a striking factor for the loss of physical functions, such as going to work, perform household chores, practicing leisure activities, prepare meals, have self-care and even the ability to take medications. 14 In large randomized clinical trial, approximately 50.0% of patients treated with high emetic risk chemotherapy were vomiting, and 58% experienced nausea, despite undergoing antiemetic therapy.…”
mentioning
confidence: 99%
See 3 more Smart Citations